521. Similarities and Differences in Transcriptomic Host Response between SARS-CoV-2 and Other Viral Infections. (31st December 2020) - Thair, Simone A; He, Yudong; Hasin-Brumshtein, Yehudit; Sakaram, Suraj; Pandya, Rushika R; Toh, Jiaying; Rawling, David C; Remmel, Melissa; Coyle, Sabrina; Dalekos, George; Koutsodimitropoulos, Ioannis; Vlachogianni, Glykeria; et al.
Abstract: Background: COVID-19 is a pandemic caused by the SARS-CoV-2 virus that shares and differs in clinical characteristics of known viral infections. Methods: We obtained RNAseq profiles of 62 prospectively enrolled COVID-19 patients and 24 healthy controls (HC). We collected 23 independent studies profiling 1, 855 blood samples from patients covering six viruses (influenza, RSV, HRV, Ebola, Dengue and SARS-CoV-1). We studied host whole-blood transcriptomic responses in COVID-19 compared to non-COVID-19 viral infections to understand similarities and differences in host response. Gene signature threshold was absolute effect size ≥1, FDR ≤ 0.05%. Results: Differential gene expression of COVID-19 vs HC are highly correlated with non-COVID-19 vs HC (r=0.74, p< 0.001). We discovered two gene signatures: COVID-19 vs HC (2002 genes) (COVIDsig) and non-COVID-19 vs HC (635 genes) (nonCOVIDsig). Pathway analysis of over-expressed signature genes in COVIDsig or nonCOVIDsig identified similar pathways including neutrophil activation, innate immune response, immune response to viral infection and cytokine production. Conversely, for under-expressed genes, pathways indicated repression of lymphocyte differentiation and activation (Fig1). Intersecting the two gene signatures found two genes significantly oppositely regulated ( ACO1, ATL3 ). We derived a third gene signature using COCONUT to compare COVID-19 to non-COVID-19 viral infections (416 genes) (Fig2). Pathway analysis did not result in significant enrichment, suggesting identification of novel biology (Fig1). Statistical deconvolution of bulk transcriptomic data found M1 macrophages, plasmacytoid dendritic cells, CD14+ monocytes, CD4+ T cells and total B cells changed in the same direction across COVID-19 and non-COVID-19 infections. Cell types that increased in COVID-19 relative to non-COVID-19 were CD56 bright NK cells, M2 macrophages and total NK cells. Those that decreased in non-COVID-19 relative to COVID-19 were CD56 dim NK cells & memory B cells and eosinophils (Fig3). Figure 1 Figure 2 Figure 3 Conclusion: The concordant and discordant responses mapped here provide a window to explore the pathophysiology of COVID-19 vs other viral infections and show clear differences in signaling pathways and cellularity as part of the host response to SARS-CoV-2. Disclosures: Simone A. Thair, PhD, Inflammatix, Inc. (Employee, Shareholder) Yudong He, PhD, Inflammatix Inc. (Employee) Yehudit Hasin-Brumshtein, PhD, Inflammatix (Employee, Shareholder) Suraj Sakaram, MS in Biochemistry and Molecular Biology, Inflammatix (Employee, Other Financial or Material Support, stock options) Rushika R. Pandya, MS, Inflammatix Inc. (Employee, Shareholder) David C. Rawling, PhD, Inflammatix Inc. (Employee, Shareholder) Purvesh Khatri, PhD, Inflammatix Inc. (Shareholder) Timothy Sweeney, MD, PHD, Inflammatix, Inc. (Employee, Shareholder)